Socialization of Digital Marketing as an Effort to Enhance the Capacity and Competitiveness of MSMEs in Jambangan Village - Lila Rahajeng; Tasnim Nikmatullah Realita (Jurnal Pengabdian Masyarakat, 2026)
Purpose: This study aims to enhance the capacity and competitiveness of MSMEs in Desa Jambangan, Malang, through digital marketing socialization, addressing limited digital literacy and restricted market access. Method: The study employed an applied research approach using a community service method conducted in three stages: preparation, implementation, and evaluation. Data were collected through observations, interviews, and documentation involving 10 MSME participants selected using purposive sampling. Practical Applications: The program introduced practical digital marketing tools such as social media, content creation applications, and online marketplaces. The results demonstrate that MSMEs were able to improve their understanding and initial skills in utilizing digital platforms for business promotion and market expansion. Conclusion: The findings indicate that digital marketing socialization effectively improves MSME capacity and supports business competitiveness. This study contributes to a practical and community-based approach to MSME digital transformation in rural areas.